2021
DOI: 10.1002/adem.202001249
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Al Alloys: The Contradiction between Strength and Electrical Conductivity

Abstract: In recent years, the severe energy consumption identified in the global powertransmission process makes the development of new generation of transmission materials with high strength (mainly the ultimate tensile strength) and outstanding electrical conductivity (EC) more urgent. Though Al and its alloys received significant attention from the scientific community in the past two decades due to their relatively high mechanical properties and excellent EC, increasing strength and EC are often incompatible in Al … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 185 publications
0
17
0
Order By: Relevance
“…Such popular Al-based systems as Al-Mg-Si (6xxx series alloys) have been developed to gain additional strengthening due to precipitation of fine second phase particles [1]. Application of additional deformation and thermal treatments of Al alloys to this and other systems makes it possible to achieve an affordable trade-off between density, strength and electrical conductivity, and such alloys have found important applications as a substitution for more expensive, less widespread, and higher density Cu-based alloys [2]. Moreover, the modern approaches for microstructural design by tuning fine-scale features, especially for complex structures [3][4][5], have provided an extra-space to further enhance both the mechanical and electrical properties of Al alloys [6].…”
Section: Introductionmentioning
confidence: 99%
“…Such popular Al-based systems as Al-Mg-Si (6xxx series alloys) have been developed to gain additional strengthening due to precipitation of fine second phase particles [1]. Application of additional deformation and thermal treatments of Al alloys to this and other systems makes it possible to achieve an affordable trade-off between density, strength and electrical conductivity, and such alloys have found important applications as a substitution for more expensive, less widespread, and higher density Cu-based alloys [2]. Moreover, the modern approaches for microstructural design by tuning fine-scale features, especially for complex structures [3][4][5], have provided an extra-space to further enhance both the mechanical and electrical properties of Al alloys [6].…”
Section: Introductionmentioning
confidence: 99%
“…The yield and tensile strengths of the alloy plates increase from 168 and 255 MPa to 171 and 263 MPa, respectively, and the elongation of the plates increased from 19% to a peak of 23% upon increasing the aging time at 120 °C from 1 h to 4 h. Upon increasing the aging time continuously to 192 h, the yield and tensile strengths of the alloy plates reach a maximum of 340 MPa and 382 MPa, respectively, and the corresponding elongation reduced to a minimum of 14%. The 7005 alloy plates exhibit an anomalous phenomena in that the strength and elongation simultaneously increase when the aging time is less than 4 h. This was not consistent with other research results obtained by most current scholars [ 20 , 21 ] that showed aluminum alloy elongation decreasing while its strength increased with increased aging time.…”
Section: Resultsmentioning
confidence: 61%
“…Besides, in applications where low weight is required, there is a need for low weight conductors pushing the development of aluminium-based materials. 1) Materials with a high specific strength combined with a low electrical resistivity are of interest both for transportation industries and for power transmission lines. For example, modern cars can contain up to 5 km of wiring comprising a significant weight, so that developing advanced Al-based conductors can assist reducing the weight and cost of automobiles together with lowering environmental impact and improving fuel efficiency.…”
Section: Introductionmentioning
confidence: 99%